Evaluation of fetal diaphragm excursion and thickness in term pregnancies complicated with pre-gestational and gestational diabetes mellitus - Gokhan Acmaz; Fatma Ozdemir; Banu Acmaz; Yusuf Madendağ; Ilknur Çöl Madendag; Iptisam Ipek Muderris (BMC, 2022)
Plain language summary The percentage of pre-gestational diabetes mellitus (PGDM) in pregnancy is 13-21% and the remaining part of diabetes is gestational diabetes mellitus (GDM). Both of the complications are related to respiratory problems at birth. Until now, it was known that this situation was due to the lack of surfactant, which has a facilitating effect on the participation of the lungs in respiration. However, in this study, the diaphragm of the babies of patients with PGDM and GDM was examined. The thickness of fetal diaphragm, movements and function were evaluated via using ultrasound. As a result, it was determined that the diaphragm movements were impaired and the babies born from these patients needed more pediatric care. This study will open horizon on new studies examining the functional capacity of the diaphragm in the future. In the future, it may be possible to decide which baby will need intensive care by examining the diaphragm.